EFISIENSI PEMASARAN TANDAN BUAH SEGAR (TBS) DI DESA BANDAR TENGGULANG KECAMATAN BABAT SUPAT KABUPATEN MUSI BANYUASIN - Kusworo, Kusworo; Iswarini, Harniatun (Universitas Muhammadiyah Palembang, 2021)
This research was conducted to analyze marketing efficiency of fresh fruit bunches. This research was conducted in Bandar Tenggulang Village, Babt Supat District, Musi Banyuasin Regency from October to December 2020. The research method used was a survey. The sampling method used was Simple Random sampling and Snowball Sampling. Data collection methods used in this study were direct observation and interviews with respondents using a list of questions that had been prepared in advance. To answer the formulation the problem, namely calculating the margin and Farmer's Share obtained from the field, it is processed in tabulation and used quantitative descriptive analysis. The results of the research show that the marketing margin of the efficient marketing channel occurs in the fourth marketing channel with a price of Rp. 1830.00 / Kg. Judging from the farmer's share occurs in the fourth marketing channel, which is 98.36%. It shows that the marketing channel for fresh bunches (FFB) in Bandar Tenggulang Village, Babat Supat District, Musi Banyuasin Regency is efficient.